Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Step-by-step explanation:
k = √(49 - 12√5)
= √(45 + 4 - 2 √180)
= √45 - √4
= 3 √5 - 2.
So, k + 2 = 3 √5 - 2 + 2 = 3 √5.
Answer:
k + 2 = 3√5
Explanation:
[tex]\sf Given: k = \sqrt{49 - 12\sqrt{5} }[/tex]
[tex]\sf \rightarrow k = \sqrt{49 - 12\sqrt{5} }[/tex]
step 1: breakdown
[tex]\sf \rightarrow k = \sqrt{4 + 45- 2 \times 2 \times 3 \sqrt{5} }[/tex]
step 2: rewrite 45 = (3√5)²
[tex]\sf \rightarrow k = \sqrt{4 + (3\sqrt{5})^2 - 2 \times 2 \times 3 \sqrt{5} }[/tex]
step 3: rearrange as per a² -2ab + b² = (a - b)²
[tex]\sf \rightarrow k = \sqrt{ (3\sqrt{5})^2 - 2 \times 3 \sqrt{5} \times 2 +2^2}[/tex]
step 4: comparing, here: a = 3√5, b = 2
[tex]\sf \rightarrow k = \sqrt{ (3\sqrt{5} -2)^2}[/tex]
step 5: simplify √a² = a
[tex]\sf \rightarrow k = 3\sqrt{5} -2[/tex]
Then find k + 2
[tex]\rightarrow \sf k = 3\sqrt{5} -2 + 2[/tex]
[tex]\rightarrow \sf k = 3\sqrt{5}[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.